SOCIALIZATION AND TRAINING IN WILD PLANT PROCESSING SUPERFOOD FOR PKK WOMEN AND PRIMARY SCHOOL CHILDREN TO OVERCOME STUNTING IN KURIPANSARI VILLAGE - S.E., M.Reg.Dev., Ph.D., Rumayya; Rahayu, Titik; Nindya, Triska; Prameswari, Zendy; Akhsani, Onish (Universitas Airlangga, 2024)
Stunting is a major nutritional problem caused by many factors such as socio-economic conditions, birth order, maternal nutrition during pregnancy and lack of nutritional intake for babies. In the case of East Java, one of the districts that has a higher stunting rate compared to the provincial and national levels in 2021 is Mojokerto Regency, especially in Kuripansari Village, Pacet District. As an effort to overcome this problem, outreach and training activities were carried out regarding the processing of superfood wild plants, namely plants or food that have a high nutritional density, are easy to find and have no economic value, as an alternative to help meet the nutritional needs of pregnant women and toddlers as well as to reduce the risk of stunting. The targets of the socialization and training program for processing wild superfood plants are PKK women (Family Welfare Programme) and elementary school children in Kuripansari Village. For PKK women, the activities carried out include the introduction and processing of superfood wild plants to enrich the availability of affordable side dishes and delicious, highly nutritious food at the household level. In elementary school children, activities carried out include socialization about nutrition and the introduction of superfood wild plants as alternative healthy and nutritious foods or snacks. The expected target is that the community can know the types of superfood wild plants and can use them to meet their nutritional needs. The results of the activities show that the outreach and training carried out have helped increase the participants' knowledge and skills in processing wild superfood plants. The advice given in this activity is the need for further assistance in the processing of superfood wild plants so that it not only has an impact on nutritional problems and stunting, but can also have an impact on the community's economy through activity development programs, for example in the form of cultivation and marketing of superfood wild plant food products. as well as educational tourism activities.